Edukasi Kanker Serviks dan Pemeriksaan PAP Smear Pada Ibu-Ibu Di RW 04 Mojosongo Surakarta - Gunawan, lucia Sincu; Wiryosoendjoyo, Kartinah; Sari, Dwi Nur Indah; KARSANTO, NARINDRO (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
The quality of public health needs to be improved through pap smear education and examination. This service activity was motivated by a lack of knowledge of cervical cancer and the willingness of residents to do pap smear examinations. The purpose of this service is to increase knowledge of cervical cancer, how to early detection and conduct pap smear examinations. This service is carried out in the form of education about cervical cancer and pap smear examination, reading of result and recommendation for prevent of cervical cancer.Â This service was carried out for 2 meetings, which were attended by 20 womenin RW 04, Mojosongo, Surakarta. The results of this service can increase the knowledge about cervical cancer and its detection. The results of pap smear tests from 20 women were declared negative for cervical cancer.